Perbandingan Kadar Glukosa dan C-Reactive Protein (CRP) pada Lansia Obesitas dan Non-obesitas di Komunitas Griya Lansia Aisyiyah Baiturrohmah Yogyakarta - Kintawarmi Kintawarmi; Nazula Rahma Shafriani; Widaninggar Rahma Putri (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Obesity is a condition of impaired body weight control system indicated by excessive fat accumulation in the body (i.e., exceeding 20% of ideal body weight) which can cause increased blood glucose levels and systemic inflammation. Obesity assessment can be measured using the Body Mass Index (BMI) and Waist Circumference Ratio (WC). The purpose of this study was to analyze the differences in glucose and CRP levels between obese and non-obese elderly in the Aisyiyah Baiturrohmah Elderly Home Community. This research method is comparative analytical observational, to see the comparison of Glucose and CRP levels in obese and non-obese elderly. The sample collection technique used the total sampling method with a cross-sectional approach with a total sample of 31 elderly (17 obese elderly and 14 non-obese elderly). The results of the study were in the form of primary data from the results of glucose examinations using the Point of Care Test method and CRP examinations using the latex agglutination method. The results of statistical analysis of glucose examinations using the one sample t-test showed a p-value of 0.001 which indicated a significant difference between obese and non-obese glucose levels. Meanwhile, statistical tests were not carried out on CRP because all samples were found to be non-reactive, so it was stated that no significant difference was found between the CRP of obese elderly and the CRP of non-obese elderly